Testing a mediation model of teacher caring, grit, and student wellbeing in English as a foreign language students - Zhou, Guanbing (Frontiers in Psychology, 2023)
This study investigated the impact of perceived teacher caring on student wellbeing in Chinese English as a Foreign Language (EFL) students, focusing on the mediating role of grit. The sample consisted of 748 EFL students from various Chinese universities. Data were collected through self-report questionnaires assessing perceived teacher caring, student wellbeing, and grit.Structural equation modeling was employed to examine the direct and indirect effects of teacher caring on student wellbeing. The results revealed a significant positive relationship between perceived teacher caring and student wellbeing. Additionally, grit was found to mediate this relationship, suggesting that students with higher levels of grit were more likely to experience greater wellbeing. These findings highlight the importance of teacher-student relationships and the role of grit in promoting student wellbeing in the EFL context. Implications for educators and future research directions are discussed.